Development of School Administration Model Based on the Sufficiency Economy Philosophy of Small-sized Schools under the Foundation of the Church of Christ in Thailand - Tongtuswattana, Prasit; Duagchuen, Patcharaporn; Intarak, Choomsak (Academic MCU Buriram Journal, 2025)
This research aimed to: 1) study the problems of school administration based on the Philosophy of Sufficiency Economy, 2) design and develop an administrative model, 3) evaluate the model, 4) compare the outcomes before and after the implementation of the model, and 5) examine the results of the model in terms of efficiency, effectiveness, and value. The sample group for identifying existing problems consisted of 12 small schools under the Foundation of the Church of Christ in Thailand. Key informants included the school director, head of academics, head of facilities, and head of student affairs-five individuals per school, totaling 65 participants. The experimental group consisted of staff from Sahabamrungwittaya School, with 12 participants. Research instruments included questionnaires, the developed model, evaluation forms, pre- and post-tests, and assessment tools for measuring efficiency, effectiveness, and value. Content validity between research questions and objectives was assessed by five experts. Statistical tools used for data analysis were frequency, percentage, mean, standard deviation, t-test, and content analysis. The research results found that: 1) The problems of school administration based on the philosophy of sufficiency economy in small schools under the foundation of the Church of Christ in Thailand are generally practiced at a low level. Considering each aspect, the problem with a medium average level is supervision and monitoring, 2) The model of school administration based on the philosophy of sufficiency economy in small schools under the foundation of the Church of Christ in Thailand is the 3-2 PASS Model (Three-Two PASS Model), consisting of 3 rings: moderation, reasoning, and immunity, with 2 conditions: knowledge and morality, 3) The results of the comparison of the experiment using the model before and after the experiment are significantly different at the .01 level, 4) The results of the model use in terms of efficiency, effectiveness, and value are at the highest level. The opinions are in the same direction and consistent with the hypothesis.